Claudia and the Perfect Boy - Martin, Ann M. (London Scholastic Inc., 1994)
While reading a magazine, Claudia comes up with the idea of starting a personals column in her school paper. She helps others, but will she ever find the perfect boy for her?
Keywords: Babysitters -- Clubs -- Children's stories